PENGUATAN EKONOMI GHARIM DALAM PERSPEKTIF ULAMA KONTEMPORER MELALUI LEMBAGA AMIL ZAKAT - Jannah, Laila Miftahul; Abdillah, Aufa (Islamic Economics Program, Faculty of Islamic Economics and Business, 2021)
This research examines how the Amil Zakat Institute handles the gharim in the view of Contemporary Ulama, with a literature review methodology, which is sourced from the main books of Fiqh written by the Imams of the madzhab, namely Imam Abu Hanifah, Imam Malik, Imam Syafi'i and Imam Hambali. Based on contemporary fiqh studies, that Gharim or people who are in debt who are entitled to receive zakat are people who do not have the assets to pay their debts. If he has wealth, it is only enough to support his daily needs.